Brothers and strangers : Black Zion, Black slavery, 1914-1940 - Sundiata, I. K. (E-Duke books scholarly collection., 2003)
An account of the rise, fall, and persistence of the 20th century's Black Zionist dream -- the movement's creation of a homeland in Africa.